A Comparison of Quran-Memorizers and Non-Memorizers' Mental Health in Gorgan - Javad Lakzaei; Akram Sanagoo; Ali Kavosi; Leila Jouybari; Abolfazl Kavosi; Zeynab Haghdost; Hossein Nasiri (Shahid Beheshti University of Medical Sciences, 2019)
For downloading the full-text of this article please click here. Background and Objective: Despite their technological advances over the past decades, human beings have not yet achieved the peace of mind, which is the foundation for a happy life as recommended by the World Health Organization. It is therefore essential to pay attention to religious teachings, especially the Holy Quran, to achieve mental health. This study aimed to compare the mental health of Quran-memorizers and non-memorizers. Method: In this case-control study, which was conducted in 2015, 101 of Quran-memorizers from Gorgan (Northern Iran) and 102 non-Quran memorizers were compared in terms of mental health. Convenience sampling method was used to select Quran-memorizers. Also, the members of non-memorizers' group were selected by matching the participants' age and gender with those of their counterparts in the Quran-memorizers' group. The data were gathered through the General Health Questionnaire (GHQ-28) and analyzed using statistical tests (i.e. Kolmogorov-Smirnov, Mann-Whitney, and One way ANOVA). The significance level was considered 0.05. All ethical issues were observed in this study and the researchers declared no conflict of interests. Results: According to the findings, total General Health in the Quran-memorizers' group was better than that of the non-memorizers (P=0.012). Moreover, Quran non-memorizers showed more symptoms of anxiety and sleep disorders (P=0.031). There was also a significant difference between the two groups in terms of depression symptoms (P<0.001). Conclusion: The results indicate that Quran-memorizers had better scores in some scales of general health (mental health) than non-memorizers in the control group. Thus, memorization of Quran can be effective in promoting mental health. For downloading the full-text of this article please click here. Please cite this article as: Lakzaei J, Sanagoo A, Kavosi A, Jouybari L, Kavosi A, Haghdost Z, Nasiri H. A Comparison of Quran-Memorizers and Non-Memorizers' Mental Health in Gorgan. J Res Relig Health. 2019; 4(5): 57- 66.